Mechanical And Biodegradation Properties Of Sago Starch Natural Rubber Latex Composites. - A.Rashid, Azura; Misman, Muhammad Afiq; Ahmad, Hairol Izmar (2010)
The purpose of this research is to investigate the effect of sago starch loading on the mechanical and biodegradation properties of Natural Rubber Latex (NRL) composites.